INFORMATION SUPPORT OF THE GEORGIA – SOUTH OSSETIA CONFLICT RESOLUTION ACTIVITY BY THE EU OBSERVER MISSION IN GEORGIA - O. S. Samutina; K. V. Yumatov (Вестник Кемеровского государственного университета, 2014)
The military conflict between Georgia, South Ossetia and Russia in August 2008 led to active involvement of the European Union in the peace-making activity. The EU Observer Mission in Georgia has been operating since October 2008. The Mission was to observe the conflict resolution and promotion of humanitarian actions for those who suffered in the warfare and the ethnical conflicts, so it became directly involved in the context of the Ossetian-Georgian, GeorgianAbkhasian and Russian-Georgian conflicts. The study of the information materials reflecting the Mission’s activity shows that its interaction with Georgia was positive, which allowed it, on the one hand, to restrain the Georgian authorities from radical military actions of 8 August 2008, but on the other hand, to create the informational image of Georgia as a country striving for peace and effective resolution of its revolting autonomy’s problems. As for Georgia’s opponents, the Mission’s activity allowed to fasten the withdrawal of Russian troops and provided Georgia with external protection from Russia’s direct power politics. The Mission’s website interprets South Ossetia, Abkhasia and Russia’s refusal to let the Mission in the observed territory for permanent work as the countries’ refusal to facilitate the real peace-making process. Thus, the idea promoted among Internet users is that the Russian authorities’ actions break the “Medvedev-Sarkozy” plan and hinder conflict resolution. So, the Mission’s activities do not correspond to the real peace-making activity, but rather to the EU’s policy to reduce Russia’s influence on the post-Soviet space.